The Society of 27 Book Lovers (1930-1940): Membership, Relationships, Atmosphere - Braziūnienė, Alma (Knygotyra, 2021)
The Society of 27 Book Lovers in Kaunas that functioned in 1930–1940 played an important role in the history of Lithuanian culture. It signified the outset of the organized bibliophilic movement in Lithuania. The society, brought together by Vytautas Steponitis, Paulius Galaunė, Viktoras Cimkauskas and other like-minded people, contributed immensely in shaping the tradition of bibliophilic activity, upraised the culture of the Lithuanian book, and developed aesthetic circulation and bibliophilic book publishing (10 publications were published). All of this was done by a dozen (ranging in number from 15 to 21) devoted book lovers and bibliophiles par excellence. Their bibliophilic hobby transcended the boundaries of amateur activities, and the Society operated as a professional publishing house giving rise to the publishing of scientific periodicals of book science. The article, based on the archives of this Society kept in the Wroblewski Library of the Lithuanian Academy of Sciences, analyses personal expression of the members of the Society, their interrelationships, seeks an answer leading to the fact that extremely prominent figures managed to get together for fruitful bibliophilic activities, examines the atmosphere that prevailed in the amateur meetings of the Society of 27 Book Lovers, publishing and various other activities in the daily life. It is not intended to bring to light all the members of the Society, the article focuses only on some of the most prominent personalities and those moments of their activity that have not been previously examined by other researchers.It was concluded that the rotation of the amateur members of the Society of 27 Book Lovers was natural, determined by various life circumstances: the Society, which launched its activities in 1931 had 15 members, and until 1940, another 12 new members joined in, however the Society lost 10 of them as well. The number of seceding members was determined by the distancing of some members from bibliophilic ideas, lack of time (professional activities, positions of high responsibility), etc. However, the core of the Society (about 10 to 12 people) remained stable at all times and ensured the productive work of the Society. The productive activities of the Society were directly influenced by the chairmen elected for the term of 3 years (V. Steponaitis, Kazys Bizauskas, Juozas Balčiūnas-Švaistas), however, other members, even without being on the board, acted as contributors to various activities.The Society operated according to a very formalized procedure (recording of meetings, board meetings, excursions and other activities, approval of minutes, etc.), however, at the same time the archives of the Society testify that a cosy amiable atmosphere of communication and a sense of humour prevailed. This group of people was of one mind, they knew each other for a long time, almost all of them were of the same generation and of similar age. Differing political views did not interfere with bibliophilic activities. The correspondence of the members of the board on the failures of the publishing of publications reveals intercommunion, the realized meaning of the cultural work, the significance of V. Steponaitis as a personality uniting the Society in its activities. The activities of the Society of 27 Book Lovers demonstrated that such work could be carried out only by a strong group of exceptional figures, the activities of whom distinctly represented the elite bibliophilia, and hence, the tradition of the organized bibliophilic movement organically stemming even from the 19th century. The 27 Book Lovers managed to extend this tradition.
Keywords: 27 Book Lovers; societies; the history of Lithuanian bibliophilia; elite bibliophilia; the history of Lithuanian culture; Vytautas Steponaitis; Viktoras Cimkauskas; Antanas Rucevičius